1982
DOI: 10.1159/000131804
|View full text |Cite
|
Sign up to set email alerts
|

Complex evolution of sex chromosomes in Gerbillidae (Rodentia)

Abstract: The sex chromosomes of 11 species of Gerbillidae (Meriones tristrami, M. crassus, M. libycus, M. persicus, M. unguiculatus, Gerbillus hesperinus, G. nigeriae, G. gerbillus, G. campestris, Gerbillurus tytonis, and Taterillus gracilis) are reported. A very complex evolution of the X chromosome and, to a lesser degree, of the Y chromosome was observed, including several inversions, translocations with autosomes, and an increase in heterochromatin. The role of constitutive heterochromatin, isolating autosome and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…; Dobigny et al, manuscript submitted for publication; present study) is also characteristic of numerous taxa within the subfamily Gerbillinae (Viegas-Péquignot et al, 1982Volobouev et al, 1995). Unfortunately, data on genetic differentiation are lacking for most of them, and therefore little is known about the rate of karyotypic changes and their correlation with the speciation process.…”
Section: Discussionmentioning
confidence: 63%
“…; Dobigny et al, manuscript submitted for publication; present study) is also characteristic of numerous taxa within the subfamily Gerbillinae (Viegas-Péquignot et al, 1982Volobouev et al, 1995). Unfortunately, data on genetic differentiation are lacking for most of them, and therefore little is known about the rate of karyotypic changes and their correlation with the speciation process.…”
Section: Discussionmentioning
confidence: 63%
“…This is in con trast to several other mammalian species which show an increase in heterochromatin coincident with Xand/or Y-autosome translocations (Benirschke et al, 1980;Ma et al, 1980;Dutrillaux et al, 1981). Viegas-Pequignot et al (1982) suggest that C-band heterochromatin may effectively separate a translo cated autosome from the original X chromosome and prevent inactivation of the translocated autosome. The translocated autosomal portion of the X would thus behave autonomously from the remainder of the X chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some species present sex chromosomes with synapsis and recombination, as in G. chiesmani, G. nigeriae, G. hoogstrali, and Taterillus pygargus [31]. However, the synapsing regions in these species seem to be originated, as in many other eutherian mammals, by recent translocations of autosomal segments to both the X and Y chromosomes [49,50]. Previous analyses on the sex chromosomal phylogeny of Gerbillidae have shown that the X chromosome of M. unguiculatus could be one of the most primitive among this family [49], reinforcing the idea that the asynaptic condition of sex chromosomes would be an ancient feature of this group.…”
Section: Lack Of Par Is Responsible For the Asynaptic Nature Of Sex Cmentioning
confidence: 99%